2015
DOI: 10.1074/jbc.m114.606228
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Fasting Identifies Heat Shock Protein 10 as a Sirtuin 3 Substrate

Abstract: Background: A distinct mechanism linking fasting-associated mitochondrial protein acetylation and increased fat oxidation is unknown. Results: Acetylation of heat shock protein 10 enhances medium-chain acyl-CoA dehydrogenase folding, enzyme activity, and fat oxidation. Conclusion: A novel acetylation-dependent mechanism modulates fat oxidation via regulating mitochondrial metabolic enzyme folding. Significance: A Sirtuin 3 deacetylase-linked mechanism to control fat oxidation via modulation of enzyme folding h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…; Lu et al . ). Following fasting, altered SIRT3 expression may contribute to the regulation of fatty acid oxidation and oxidative metabolism in murine skeletal muscle (Shi et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Lu et al . ). Following fasting, altered SIRT3 expression may contribute to the regulation of fatty acid oxidation and oxidative metabolism in murine skeletal muscle (Shi et al .…”
Section: Introductionmentioning
confidence: 97%
“…While the extent of LCAD hyperacetylation was lower in Alrob's study (?50 %) compared to our study (?400 %), the explanation for different results in probably identical SIRT3 -/-mice with similarly low fat content (12 % by calories) in the food remains to be elucidated. Of note, Lu and colleagues recently reported that increased acetylation of the K56 residue of Hsp10 in the absence of SIRT3 may alter the binding affinities between Hsp10 and Hsp60, which in turn may enhance the capacity to appropriately fold MCAD, resulting in increased enzyme activity and overall fatty acid oxidation [29]. Thus, besides regulating energy metabolic rates by directly modulating metabolic enzyme acetylation, additional mechanisms seem to exist by which SIRT3 may regulate energy metabolism, which have not been investigated in our study or the study by Alrob and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Also uncertain is whether global shifts in lysine acetylation have a physiologically relevant impact on cellular function, especially considering that many of these events appear to occur at low stoichiometry (Baeza et al, 2014; Weinert et al, 2015). Nonetheless, a growing number of studies using site-directed mutagenesis strategies show that at least some of these modifications alter activity of mitochondrial proteins, mostly in a negative direction (Hallows et al, 2006; Hallows et al, 2011; Hirschey et al, 2010; Still et al, 2013), although gain-of-function acetylation events have been reported (Fernandes et al, 2015; Lu et al, 2015). Lysine acetylation has also been linked to nutrient control of autophagy and mitophagy (Webster et al, 2014).…”
Section: Discussionmentioning
confidence: 99%